Revisión bibliográfica de los protocolos de manejo de biocontroladores (Chrysopidae) en su captura, aislamiento y propagación, Salache – Ceypsa, Latacunga. 2020 – 2021. - Córdova Reascos, Mishell Andreina (2021)
The Chrysopa is an insect belonging to the Chrysopidae family, in their larval stage they are polyphagous predators of several pests of agricultural interest. Ecuador ranks tenth in the world in the use of pesticides, which is why information should be sought about new alternatives for pest control. Thus, the main objective of this work is to carry out a bibliographic review of the protocols for the capture, isolation and propagation of Chrysopidae for their use as a bio controller. The methodology used in this research was mainly based on the identification of the problem, information search, bibliographic management, cleaning, database coding and systematization of the information collected from the last 10 years (2010-2021). Finding 50 documents out of 118 inserted in the database make reference to the main trapping methods for lacewing which are the use of entomological net, light traps, cloth or plastic with baits and entomological aspirators, focusing mainly on the capture of adults. For isolation methods 86 files suggest that this procedure should be adapted to the life cycle of the insect, so that the adults are placed together, the larvae are individualized due to their cannibalistic nature and the eggs are placed in small containers to ensure their correct embryonic development. The propagation methods in 58 files explain that the basis for its realization is the pairing of adult insects for the subsequent oviposition of females in different types of substrates. These methods are also adapted to the criteria and needs of the researcher in terms of exposure to light hours, temperature, relative humidity and diet of the insects.